N. Chester, The English Administrative System. 1780-1870 - Hubert Izdebski (Czasopismo Prawno-Historyczne)
Recenzja: Norman Chester, The English Administrative System. 1780-1870. Oxford, Clarendon Press 1981, ss. XIV, 398, indeks.